Design of the Polish Colonoscopy Screening Program: a randomized health services study - Kaminski, Michal F.; Kraszewska, Ewa; Rupinski, Maciej; Laskowska, Milena; Wieszczy, Paulina; Regula, Jaroslaw (Endoscopy, 2015)
Background and study aims: Colonoscopy screening for colorectal cancer has been implemented without evidence from randomized controlled trials quantifying its benefit and invariably as an opportunistic program, both of which are contrary to the European Union guideline recommendations. The aim of this paper is to describe the rationale and design of the first population-based colonoscopy screening program (PCSP), which was launched in Poland in 2012 as a randomized health services (RHS) study.Methods: The PCSP is a natural extension of opportunistic colonoscopy screening implemented in 2000. It uses colonoscopy capacity, a quality assurance program, and a network of 92 centers built up during the opportunistic screening phase to develop a countrywide PCSP. Within the PCSP, single screening colonoscopy is offered to a target population aged 55 – 64 years. The PCSP uses an RHS design, which means that eligible individuals drawn from population registries are randomly assigned to immediate or postponed invitation to screening. Individuals from birth cohorts that will reach the upper age limit for screening before full implementation of the PCSP are randomly assigned, in a 1:1:1 ratio, to “immediate” screening, “postponed” screening, or a “never invited” control group. The RHS design is a natural platform that will evaluate the effectiveness of screening, and compare different age ranges for screening, invitation procedures, and quality improvement interventions. Up to 2015, 24 centers have been developed, with 34.2 % geographic coverage and 851 535 individuals enrolled.Conclusions: The PCSP sets an example for implementation of population-based colonoscopy screening with experimental design to ensure proper evaluation of its effectiveness.RHS registration number: 007_2015_1_RHS.